66 Relationship Between Health-related Quality of Life and Efficacy in the Phase 3 LITESPARK-005 Study of Belzutifan versus Everolimus in Previously Treated Advanced Clear Cell Renal Cell Carcinoma - Pooja Ghatalia; Thomas B Powles; Laurence Albiges; Katriina Peltola; Guillermo de Velasco; Mauricio Burotto; Cristina Suarez; Elaine T Lam; Roberto Iacovelli; Mahmut Gumus; Elena Verzoni; Christian Kollmannsberger; et al. (The Oncologist, 2026)
Abstract Background In the randomized phase 3 LITESPARK-005 study (NCT04195750), belzutifan significantly improved progression-free survival (PFS) and objective response rate, but not overall survival (OS), when compared with everolimus in participants with advanced clear cell renal cell carcinoma (ccRCC) previously treated with an immune checkpoint inhibitor and antiangiogenic therapy. Patient-reported outcomes (PROs) assessed using the Functional Assessment of Cancer Therapy-Kidney Cancer Symptom Index–Disease Related Symptoms (FKSI-DRS) and the EORTC Quality of Life Questionnaire Core 30 (QLQ-C30) global health status/quality of life (GHS/QoL) favored belzutifan. We conducted a post hoc analysis to evaluate associations between health-related quality of life (HRQoL) and clinical outcomes after >2 years of minimum follow-up. Methods Adults with advanced ccRCC were randomly assigned 1:1 to oral belzutifan 120 mg or everolimus 10 mg once daily until progression or unacceptable adverse events. This post hoc analysis population included all treated participants with ≥1 PRO assessment using the FKSI-DRS and QLQ-C30 GHS/QoL. Associations between HRQoL (baseline, longitudinal time-dependent changes, and landmark time points at weeks 13, 25 and 53) and PFS and OS were evaluated using Cox proportional hazards models. Clinically meaningful improvement from baseline was defined as a ≥ 3‑point increase for FKSI‑DRS and a ≥ 10‑point increase for QLQ‑C30 GHS/QoL per established thresholds. Landmark analysis excluded participants with events prior to each time point. No adjustments were made for multiplicity, and no formal hypothesis testing was performed. Results A total of 720 participants were included (belzutifan, n = 366; everolimus, n = 354), with a median study follow-up of 35.8 months (range, 26.9-49.2). Higher baseline FKSI-DRS scores were associated with modest PFS (hazard ratio [HR], 0.91; 95% CI, 0.86-0.96) and OS (HR, 0.86; 95% CI, 0.81-0.91) benefit. Higher baseline QLQ‑C30 GHS/QoL scores were not associated with PFS benefit (HR, 0.98; 95% CI, 0.94-1.03) but were associated with a small OS benefit (HR, 0.92; 95% CI, 0.88-0.96). In longitudinal analyses, improvement in FKSI-DRS was associated with lower risk of progression or death (HR, 0.80; 95% CI, 0.74-0.85) and death (HR, 0.57; 95% CI, 0.53-0.62); similar associations were observed for QLQ-C30 GHS/QoL (PFS: HR, 0.80; 95% CI, 0.74-0.85; OS: HR, 0.64; 95% CI, 0.60-0.69). In landmark analyses, participants with stable or improved HRQoL at weeks 13, 25, and 53 had numerically longer PFS and OS compared with those with deterioration, although estimates were imprecise at later time points (Table). Conclusions In this exploratory post hoc analysis of LITESPARK-005, higher baseline HRQoL and improvements during treatment were associated with improved PFS and OS in advanced ccRCC. These hypothesis-generating findings support HRQoL as a potential prognostic marker; however, given the pooled treatment arms and potential for time-dependent confounding and reverse causation, results should be interpreted cautiously.